ETV2 primes hematoendothelial gene enhancers prior to hematoendothelial fate commitment - Jeffrey D. Steimle; Chul Kim; Megan Rowton; Rangarajan D. Nadadur; Zhezhen Wang; Matthew Stocker; Andrew D. Hoffmann; Erika Hanson; Junghun Kweon; Tanvi Sinha; Kyunghee Choi; Brian L. Black; et al. (Cell Reports, 2023)
Summary: Mechanisms underlying distinct specification, commitment, and differentiation phases of cell fate determination remain undefined due to difficulties capturing these processes. Here, we interrogate the activity of ETV2, a transcription factor necessary and sufficient for hematoendothelial differentiation, within isolated fate intermediates. We observe transcriptional upregulation of Etv2 and opening of ETV2-binding sites, indicating new ETV2 binding, in a common cardiac-hematoendothelial progenitor population. Accessible ETV2-binding sites are active at the Etv2 locus but not at other hematoendothelial regulator genes. Hematoendothelial commitment coincides with the activation of a small repertoire of previously accessible ETV2-binding sites at hematoendothelial regulators. Hematoendothelial differentiation accompanies activation of a large repertoire of new ETV2-binding sites and upregulation of hematopoietic and endothelial gene regulatory networks. This work distinguishes specification, commitment, and sublineage differentiation phases of ETV2-dependent transcription and suggests that the shift from ETV2 binding to ETV2-bound enhancer activation, not ETV2 binding to target enhancers, drives hematoendothelial fate commitment.